2023
DOI: 10.1097/ta.0000000000004066
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of conducting a military-relevant multicenter cohort study to assess outcomes of early trauma resuscitative interventions in a prolonged care civilian setting

Abstract: BACKGROUND The Epidemiology and Outcomes of Prolonged Trauma Care (EpiC) study is a 4-year, prospective, observational, large-scale epidemiologic study in South Africa. It will provide novel evidence on how early resuscitation impacts postinjury mortality and morbidity in patients experiencing prolonged care. A pilot study was performed to inform the main EpiC study. We assess outcomes and experiences from the pilot to evaluate overall feasibility of conducting the main EpiC study. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…The authors reported that delayed transfer patients had higher SOFA scores. 32 While not a traditional trauma scoring tool, SOFA was selected in EpiC by a 20-member expert panel 33 as a trade-off between high feasibility of collecting the necessary clinical variables despite slightly lower performance characteristics compared with other trauma multiorgan failure scoring tools. 21,34 The correlation of critical interventions with organ failure scores and trends, especially as they pertain to prolonged periods of resuscitation and delays to care, will be an ongoing area of focus in the EpiC study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The authors reported that delayed transfer patients had higher SOFA scores. 32 While not a traditional trauma scoring tool, SOFA was selected in EpiC by a 20-member expert panel 33 as a trade-off between high feasibility of collecting the necessary clinical variables despite slightly lower performance characteristics compared with other trauma multiorgan failure scoring tools. 21,34 The correlation of critical interventions with organ failure scores and trends, especially as they pertain to prolonged periods of resuscitation and delays to care, will be an ongoing area of focus in the EpiC study.…”
Section: Discussionmentioning
confidence: 99%
“… 13 In EpiC, demographic and clinical data are collected on included patients, defined as patients with trauma (external application of force to the body) who are 18 years and older with a clinical encounter at 1 of the 10 study sites. Exclusion criteria include prisoners, injury onset exceeding 24 hours before arrival at the first study site, stings, other forms of envenomation, toxicologic injuries, drownings, patients who are found deceased on scene, and/or patients transported via private EMSs agency 13 . Data are collected by a team of trained research personnel using primary review of EMSs, hospital, and pathology records for each case.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations